Cyclopropylamine plasma polymers deposited onto quartz crystal microbalance for biosensing application. Issue 12 (22nd October 2014) - Manakhov, Anton; Skládal, Petr; Nečas, David; Čechal, Jan; Polčák, Josef; Eliáš, Marek; Zajíčková, Lenka
<x xml:space="preserve">Abstract</x> Biosensors have been extensively developed and applied for biomedical and environmental studies. Although there are many different types of biosensing techniques, all these methods require immobilization of biomolecules. Therefore, this is a critical issue in the development of any sort of biosensor affecting its operational properties. In this work, we address this critical issue by employing cyclopropylamine plasma polymerization to deposit stable amine thin films on the surface of quartz crystal microbalance (QCM) biosensors. The antibody specific to human serum albumin (anti‐HSA) is attached to the QCM surface via cross‐linkage obtained by intermediate reaction with glutaraldehyde. All steps of the bio‐immobilization are controlled by XPS and FTIR to characterize surface and layer (bulk) chemistry. The results obtained with the antibody linked through the CPA plasma‐polymerized layer are comparable with the results obtained previously when the same antibody AL‐01 was linked to the surface using the self‐assembled thiol monolayer based on cystamine.<inline-graphic xlink:href="ark:/27927/pgh2qw7f9sg" content-type="pssa201431399-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />